Instructional Leadership Management for Teachers in Indonesia - Rita Prima Bendriyanti; Citra Dewi; Suwarni (CV. Creative Tugu Pena, 2025)
In the context of education in Indonesia, the quality of learning is largely determined by the effectiveness of instructional leadership implemented by school leaders, especially principals. Instructional leadership plays an important role in guiding teachers to improve the quality of teaching, learning planning, and student learning outcomes. Unfortunately, many teachers in Indonesia still face challenges in terms of academic supervision, development of pedagogical competence, and lack of collaborative culture supported by strong leadership management. Therefore, it is necessary to conduct an in-depth study on how the instructional leadership model can be managed strategically in the context of Indonesian education. This study aims to analyze the role and strategies of instructional leadership management in supporting teacher performance in Indonesia. Specifically, this study explores best practices, implementation barriers, and the contribution of instructional leadership to teacher professional development and improving the quality of learning. The method used is qualitative research based on literature review, by reviewing various scientific articles, education policy reports, and relevant academic publications from the last 5 years. The analysis was conducted thematically to identify patterns, approaches, and strategic implications of instructional leadership practices in Indonesian schools. The results of the study show that the success of instructional leadership is greatly influenced by the principal's ability to build a learning vision, provide professional support to teachers, and create a conducive school climate. In addition, teacher involvement in decision-making and ongoing training has been shown to increase learning effectiveness. Instructional leadership is an important pillar in education management in Indonesia. Strengthening the principal's managerial function, collaboration of teaching teams, and support for education policies are essential to ensure that instructional leadership can contribute to improving teacher quality and student learning outcomes sustainably.